2002
DOI: 10.1161/01.hyp.0000035858.04434.03
|View full text |Cite
|
Sign up to set email alerts
|

Goal-Oriented Hypertension Management

Abstract: Abstract-Several clinical trials using a blood pressure (BP) treatment algorithm focused on a predetermined goal have achieved better control rates than those of national survey data. These trials reached the Sixth Joint National Committee on the Prevention, Detection, Evaluation and Treatment of High Blood Pressure (JNC VI) diastolic blood pressure (DBP) goal of Ͻ90 mm Hg in Ͼ90% of volunteers and systolic blood pressure (SBP) goal of Ͻ140 mm Hg in Ͼ60% of volunteers. We evaluated BP control of 437 consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(7 citation statements)
references
References 21 publications
0
6
1
Order By: Relevance
“…In this study, 42.7% and 40% of the participants reached target SBP and DBP, respectively. The proportion achieved the target SBP and DBP were lower than those reported in the studies conducted in Australia [15] and USA [17, 18]. This discrepancy might be due to race [19, 20], low socioeconomic status, poor adherence to standard guidelines, inappropriate choice of antihypertensive drugs by clinicians [6], poor adherence to treatment by hypertensive patients, physician inertia, deficiencies of healthcare systems in their approach to chronic diseases [21], lack of drug availability at health facility, unaffordability of drugs by patients, and less aggressive treatment [22].…”
Section: Discussioncontrasting
confidence: 61%
“…In this study, 42.7% and 40% of the participants reached target SBP and DBP, respectively. The proportion achieved the target SBP and DBP were lower than those reported in the studies conducted in Australia [15] and USA [17, 18]. This discrepancy might be due to race [19, 20], low socioeconomic status, poor adherence to standard guidelines, inappropriate choice of antihypertensive drugs by clinicians [6], poor adherence to treatment by hypertensive patients, physician inertia, deficiencies of healthcare systems in their approach to chronic diseases [21], lack of drug availability at health facility, unaffordability of drugs by patients, and less aggressive treatment [22].…”
Section: Discussioncontrasting
confidence: 61%
“…It has been observed that restrictions in diuretic use were the primary cause of resistant hypertension in patients with CKD [156]. Restricted diuretic use includes either lower doses or inappropriate drug selection; thiazides are usually not effective when GFR is lower than 40 and should, therefore, be replaced by loop diuretics in such patients.…”
Section: Chronic Kidney Diseasementioning
confidence: 99%
“…Another contributor to treatment resistance is the use of inappropriate drug combinations or suboptimal doses of antihypertensive drugs. Indeed, a study of patients with resistant hypertension revealed that simple measures, such as increasing diuretic dosing or switching to appropriate diuretics, can result in significant blood pressure reductions [156]. …”
Section: Rational For the Management Of Resistant Hypertensionmentioning
confidence: 99%
“…This indicates that treating blood pressure is much less effective in controlling blood pressure in Japan. This could be the result of differences in aggressiveness of treatment, different drug regimens [13] , drug titration, patient compliance with medication [14] , physician compliance with recommended blood pressure levels [15] , or resistance of hypertension to treatment [13] .…”
Section: Resultsmentioning
confidence: 99%